Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Yang Mengalami Amnesia Karena Trauma Berat Menurut Pasal 44 Undang-Undang No. 1 Tahun 1946 Tentang Kitab Hukum Pidana - Kurnia, Seza Aulia Gusti (Media Hukum Indonesia (MHI), 2026)
This study examines the criminal liability of perpetrators of serious assault who experience amnesia as a result of depression triggered by severe trauma. The method used is normative juridical, with a statutory and conceptual approach. The study focuses on the application of Article 44 of the Criminal Code No. 1 of 1946, criminal responsibility theory, and expert doctrine. Furthermore, this research integrates clinical psychology and psychiatric perspectives in understanding amnesia and depression to assess their impact on the perpetrator's capacity to be accountable for their actions. The results indicate that amnesia resulting from depression and severe trauma does not automatically negate the ability to be criminally responsible, unless it can be proven that the disorder caused the perpetrator to be unable to understand or control their actions at the time of the crime. Therefore, the application of Article 44 of the Criminal Code in cases of serious assault with amnesia requires a comprehensive medical and legal assessment to ensure that the verdict reflects substantive justice.